Superalloys 718, 625, 706 and Various Derivatives (1997) 1997
DOI: 10.7449/1997/superalloys_1997_521_530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minor Elements on Microstructure and Mechanical Properties of In 718 Alloy

Abstract: The effects of minor elements, P, S and Si, on microstructure and mechanical properties of In 718 alloy were investigated. It is shown that decreasing P content causes the appearance of a film-like 6 phase, while increasing Si content promotes the formation of Laves and M6C phases and reduction of the precipitation of 6 phase. The most striking effect is that the stress rupture life prolonged nearly 4 times and the stress rupture ductility rose over 4 times when the P content increased from 0.0008% to 0.013%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The effect of the individual elements could not be separated but the Laves phase was enriched in Si compared with the matrix whereas it was depleted in Fe, suggesting that Si has a direct influence on TCP phase formation whereas the effect of Fe, if present, is indirect. An increase in Si content has also been shown by others to promote Laves phase formation 57 and to result in its enrichment in the precipitates. 57,58 Recent work on Laves phase in steels by Isik et al 59,60 has also shown Si enrichment in Laves precipitates.…”
Section: Effect Of Individual Elementsmentioning
confidence: 74%
See 1 more Smart Citation
“…The effect of the individual elements could not be separated but the Laves phase was enriched in Si compared with the matrix whereas it was depleted in Fe, suggesting that Si has a direct influence on TCP phase formation whereas the effect of Fe, if present, is indirect. An increase in Si content has also been shown by others to promote Laves phase formation 57 and to result in its enrichment in the precipitates. 57,58 Recent work on Laves phase in steels by Isik et al 59,60 has also shown Si enrichment in Laves precipitates.…”
Section: Effect Of Individual Elementsmentioning
confidence: 74%
“…An increase in Si content has also been shown by others to promote Laves phase formation 57 and to result in its enrichment in the precipitates. 57,58 Recent work on Laves phase in steels by Isik et al 59,60 has also shown Si enrichment in Laves precipitates. In addition, precipitation of Laves phase adjacent to M 23 C 6 precipitates due to local enrichment of Si and P was seen.…”
Section: Effect Of Individual Elementsmentioning
confidence: 74%
“…The extruded sample has been homogenised and during the latter process, the Si from the laves phase dissolved in the matrix of the alloy accounting for the higher Si content. However, this difference is unlikely to affect the mechanical properties [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ideal can even be less than 5ppm. Minor Elements Control Besides controlling harmful elements, a series of studies on optimizing minor elements such as P, B, Zr, and Mg have also been carried out in China to improve the performances of superalloys [4][5][6][7][8][9][10]. One of the significant efforts involved is optimization of phosphorus in GH4169, whose content had always been controlled under 50ppm, and once been pursued to the "ultra-low" level as it was initially considered harmful to the alloy.…”
Section: Introductionmentioning
confidence: 99%